Development of a problem-posing multimedia module and its effectiveness to enhance student performance in form four biology - Ab. Wahid, Nor Tutiaini (2019)
Learning and teaching activities in education are crucial in presenting permanent and meaningful learning to science students. This study aims to develop Problem-Posing Multimedia Module (PROPOSE-M) and to test its effectiveness in enhancing students‘ performance in Biology subject as compared to the traditional teaching method (TRAD). This study extends the Cognitive Theory of Multimedia Learning (CTML) by integrating it with the problem-posing instructional strategy (PPIS) that championed the skills of communication, collaboration, creativity, and critical thinking. This study applied Design and Development Research (DDR) approach. ADDIE model (Analyse, Design, Develop, Implement and Evaluate) was used to develop PROPOSE-M. Three research questions were formulated for this study; (1) What are the components needed to develop PROPOSE-M for teaching the concept of osmosis and diffusion among Form Four Biology Students? (2) Is there any significant difference in the mean score between the PROPOSE-M and the traditional teaching method (TRAD) group? (3) To what extent PROPOSE-M could enhance student‘s conceptual change compared to TRAD? To seek the answers, a sequential mixed method approach encompassing interview, survey and quasi-experimental techniques was adopted. Two groups of students from two different schools in Petaling Perdana District were involved in the study of which are the experimental group (PROPOSE-M) (n=31) and one control group (TRAD) (n=30), and both groups have equivalent characteristics. Students' performance was analysed using the mean score of pre-test, post-test and retention-test. The main findings show that the mean scores of students who were exposed to newly-developed PROPOSE-M are significantly higher to students who were exposed to TRAD in post-test with t (47) = 2.866, p < .05. The results from retention-test also revealed that PROPOSE-M has not just enhanced students' conceptual understanding but also retained students' memory longer compared to TRAD with t (59) = 3.845, p < .05. PROPOSE-M also could enhance students' performance in both LOTS and HOTS as it builds conceptual change among students. The implication of this study can be seen in terms of practice in the school context in which it provides an alternative tool for teaching and learning Biology. Further, this study also provides an instructional model as a guideline that could benefit teacher in planning steps to be taken to encourage problem-posing in Biology curriculum.